2014
DOI: 10.1210/jc.2013-3027
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Running Reduces Parathyroid Hormone Concentrations During Recovery Compared With a Nonexercising Control Group

Abstract: Lower PTH concentrations after acute endurance running compared with a rested control condition suggest a true effect of exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 43 publications
3
9
0
Order By: Relevance
“…In the study by Li et al (2014), blood estradiol concentration increased significantly in ovariectomized rats after treatment using voluntary wheel running exercise, and such changes in concentration was attributed to the appropriate exercise intensity 32 . These results supported the findings by Kim (2012) and Scott et al (2014) on moderate-intensity aerobic exercise using a treadmill 30 , 33 and Stringhetta-Garcia et al (2016) on resistance exercise showed that the serum estradiol levels were decreased or similar compared to the levels of control group (ovariectomized) 34 . Therefore, it is believed that additional studies in accordance with the exercise intensity are needed to accurately identify factors that impact lipid and bone metabolism and changes in the blood estradiol concentration based on exercise after ovariectomy.…”
Section: Discussionsupporting
confidence: 88%
“…In the study by Li et al (2014), blood estradiol concentration increased significantly in ovariectomized rats after treatment using voluntary wheel running exercise, and such changes in concentration was attributed to the appropriate exercise intensity 32 . These results supported the findings by Kim (2012) and Scott et al (2014) on moderate-intensity aerobic exercise using a treadmill 30 , 33 and Stringhetta-Garcia et al (2016) on resistance exercise showed that the serum estradiol levels were decreased or similar compared to the levels of control group (ovariectomized) 34 . Therefore, it is believed that additional studies in accordance with the exercise intensity are needed to accurately identify factors that impact lipid and bone metabolism and changes in the blood estradiol concentration based on exercise after ovariectomy.…”
Section: Discussionsupporting
confidence: 88%
“…In this regard, two days of exercise significantly increased serum Ca, phosphorus and Ca/phosphorus ratio levels in elderly mice, while no significant change in these markers was reported after 3 and 8 weeks of exercise, nevertheless in line with the present study, bone density and strength significantly increased after long-term exercise in 16-month-old mice (16). Researchers have shown that exercise modulates the parathyroid hormone levels, but has no significant effect on Ca and phosphorus in young men (18); also, combined endurance and strength trainings increased bone strength by reducing parathyroid hormone levels, reducing inflammatory cytokines, and increasing osteocalcin (19).…”
Section: Discussionsupporting
confidence: 87%
“…Although the mechanism is still unclear, an increased running distance may potentially influence increased PTH concentration. PTH concentration has been reported to be transient-increase dependent on exercise intensity and duration [ 20 , 21 ]. In addition, teriparatide (recombinant human PTH), a therapeutic osteoporosis drug, has been reported to decrease 25(OH)D concentration [ 22 ].…”
Section: Discussionmentioning
confidence: 99%